2019
DOI: 10.1002/ece3.5662
|View full text |Cite
|
Sign up to set email alerts
|

Dietary specialization is conditionally associated with increased ant predation risk in a temperate forest caterpillar community

Abstract: The enemy‐free space hypothesis (EFSH) contends that generalist predators select for dietary specialization in insect herbivores. At a community level, the EFSH predicts that dietary specialization reduces predation risk, and this pattern has been found in several studies addressing the impact of individual predator taxa or guilds. However, predation at a community level is also subject to combinatorial effects of multiple‐predator types, raising the question of how so‐called multiple‐predator effects relate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…These results lead me to conclude that use of multiple Crotalaria host plants, as well as a mixed diet on leaves and green seeds, by U. ornatrix is maintained by the interaction of food plant quality and defence conferred, as has been observed for other systems (Mira & Bernays, 2002;Singer & Stireman III, 2003;Rodrigues et al, 2010;Rodrigues & Freitas, 2013;Murphy & Loewy, 2015). This interaction between plant quality and defence raises the hypothesis that selection pressure for host plant use exerted by plant quality and predators varies with changes in predator communities and is therefore context-dependent (Katsanis et al, 2016;Singer et al, 2019). In communities where predation F I G U R E 4 Mean (+ 95% confidence interval) proportion of Utetheisa ornatrix adults reared on four Crotalaria species eaten by Lycosa erythrognatha in laboratory biossays: main effect of (A) host plant diet, and (B) the tissue (leaves or pods) on which larvae were reared.…”
Section: Discussionmentioning
confidence: 73%
“…These results lead me to conclude that use of multiple Crotalaria host plants, as well as a mixed diet on leaves and green seeds, by U. ornatrix is maintained by the interaction of food plant quality and defence conferred, as has been observed for other systems (Mira & Bernays, 2002;Singer & Stireman III, 2003;Rodrigues et al, 2010;Rodrigues & Freitas, 2013;Murphy & Loewy, 2015). This interaction between plant quality and defence raises the hypothesis that selection pressure for host plant use exerted by plant quality and predators varies with changes in predator communities and is therefore context-dependent (Katsanis et al, 2016;Singer et al, 2019). In communities where predation F I G U R E 4 Mean (+ 95% confidence interval) proportion of Utetheisa ornatrix adults reared on four Crotalaria species eaten by Lycosa erythrognatha in laboratory biossays: main effect of (A) host plant diet, and (B) the tissue (leaves or pods) on which larvae were reared.…”
Section: Discussionmentioning
confidence: 73%
“…Predation risk has also been hypothesized to promote the emergence of individual foraging specialization within populations if perceived risk varies among individuals (Araújo et al, 2011). For instance, increased predation from ants and birds led to a reduction in individual diet breadth in caterpillars, Lepidoptera (Singer et al, 2019). Despite parallel growth of the "animal personality" and the "individual foraging specialization" research areas, and overlap in key features (e.g.…”
Section: Accepted Articlementioning
confidence: 99%
“…Because foraging specialization has been documented to be stronger in the context of high intraspecific competition (Ratcliffe et al, 2018;Sheppard et al, 2018), we predicted a stronger trait correlation when competition was high. Similarly, with specializations being stronger in high predation contexts (Singer et al, 2019) one could also expect stronger trait correlations when predator abundance was high. Juvenile lemon shark exploration score was, however, previously found to predict distance from the shore in the subpopulation with the lowest predator abundance (North Sound), but not in the neighbouring subpopulation with high predation risk (Sharkland; Dhellemmes, Finger, Smukall, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, ants had weak and often negligible predation effects on caterpillars in this study and no cascading effects on leaf damage (Anderson et al, unpublished). Additionally, prior work on the same study system revealed that ants selectively suppress dietary specialist caterpillars while birds prefer dietary generalist caterpillars (Singer et al, 2014(Singer et al, , 2017(Singer et al, , 2019. Because we seek to study how trophic cascades are impacted by the extreme generalist gypsy moth, our focus remains on the effect of birds.…”
Section: Bird Exclusionmentioning
confidence: 99%